The role of conditionality and control in social assistance entitlement - Leskošek, Vesna; Dragoš, Srečo (Ревија за социјална политика/Journal of Social Policy, 2019)
Conditionality in social assistance delivery secured a firm foothold in the social policies of EU countries and wider. And yet, the analyses of it indicates that the aim behind it was not to resolve the poverty issues and other social problems, but to reduce social expenditure. To integrate social policy into economic policy according to the labour market demands, a series of measures that underrate social complexity were introduced, for example, user motivation, “nudging” practices guiding the users towards desired choices, incentives and punishment for wrong choices. Changes in social policy affect professionalism in social services which is expected to adjust its methods to the new requirements and thus resorts to ever more controlling and punitive practices. The article presents the case of Slovenia which adopted the ideas of strong conditionality in 2005, during the first neo-liberal government. The study focuses on behavioural economics which has become part of public policies in general.